The SMEs' internationalization: Multicriteria-Based Priorization Using Fuzzy Logic (2016)
Purpose. Develop a model based on a frame logic to quantify SMEs' internationalization by integrating linguistic variables such as human talent, infrastructure, innovation strategies, FTAs, marketing strategy and finance, among others.It is argued that the company management of international markets depends on internal factors, especially the capabilities and resources available, based on the premise that the profits made by a company depend on external factors (competitive environmental features) and internal factors (the integration of resources available), those latter are perhaps this research's biggest challenge, because it is required to propose a suitable battery of capabilities and define their importance and strategic relevance to building competitive advantages. Design/ Methodology/Approach. Fuzzy inference system is proposed to model the resources, skills and competencies that determine internationalisation success. Data: 157 linguistic variables are used, arisen from entrepreneurs, experts, consultants and researchers in international trade, and through expert judgment, 18 factors explaining export capabilities are defined. The proposed model is applied by means of a case study of the textile and clothing cluster in Medellin, Colombia. Findings. In model's implementing it got a particular global index of 28.2 for internationalisation capabilities. The result confirms the hypothesis that the capabilities and resources currently available to the sector analyzed, are not sufficient for a successful integration into the international market, and most importantly, specifies the factors and variables to intervene to improve the export's capability. Limitations. In the particular case of textile companies, is highlighted the lack of a continuous information record and very few studies directed towards the long-term plans development. Similarly, there is little consistency in the exports criteria. Originality/Value. Method emerges as an innovative management tool, linked to internal organizational spheres and their different abilities. Keywords: Fuzzy Set Methods, Exports, Strategy and Business Strategy.